+0  
 
0
74
1
avatar

If we express 3x^2 - 8x - 2 in the form a(x - h)^2 + k, then what is a + h + k?

 Nov 19, 2020
 #1
avatar+116125 
0

3x^2  - 8x  - 2   factor  out  the 3

 

3 [ x^2   -(8/3)x  - 2/3   ]  

 

Take  (1/2)  of (8/3)  =  8/6 = 4/3.....square this  = 16/9....add and subtract it witih the parentheses

 

3 [ x^2 - (8/3)x + 16/9  - 2/3 - 16/9  ]       factor the first three terms, simplify  the rest 

 

3[ (x - 4/3)^2  -  18/27 - 48/27 ]

 

3 [ ( (x - 4/3)^3  -   66/27 ]        distribute the 3

 

3(x - 4/3)^2  -  66/9

 

a + h + k =   3  + 4/3 - 66/9    =     27/9  + 12/9  - 66/9  =    - 27/ 9  =   -3

 

cool cool cool

 Nov 19, 2020

12 Online Users

avatar
avatar
avatar